Bibliometric Analysis of Trends in Scientific Publication on Culture Chachapoyas - Zubiate, Franz Tito Coronel; Salazar, Carlos Alberto Hinojosa; Vega , Heber Isac Arbildo; Huamán, Sara Emilia Remuzgo; Huatuco, Sonia Edith Limas; Chichipe , Marlyn Danila Perez (Journal of Ecohumanism, 2024)
The bibliometric analysis sought to evaluate the scientific production related to the Chachapoyas culture and to provide a systematic and quantitative understanding of the current state of research in this field. Comprehensive searches were conducted in the Scopus database using the defined search criteria limiting the search to scientific articles published in scientific journals until September 2023. The results were exported in a format that allowed subsequent analysis. Relevant bibliographic data were extracted from the search results, including article title, authors, year of publication, abstract and citations. A number of bibliometric metrics were calculated, such as number of publications per year totaling 40, the number of citations per article totaling 354, and the most frequent keyword was Peru with 17 occurrences. The author with the highest number of publications was Toyne J.M. with 9 papers and the journal with the most publications was the International Journal of Osteoarchaeology with 4. The bibliometric analysis shows a constant production in the research of the Chachapoyas Culture, with international collaboration and influential studies. However, there is still much to study and discover about this important pre-Columbian culture.